PERKEMBANGAN STRATEGI BISNIS PT UNILEVER (TINJAUAN ANALISIS PESTEL DAN SWOT) - Dhenabayu, Riska; Kamila, Fanisa Ayu Cahya; Wahyuni, Dwi; Armawadin, Irsyad Daffa; Akbar, Muhammad Farhan (Universitas Negeri Surabaya, 2022)
The purpose of this study is twofold: first, to examine how PT Unilever utilizes analytical tools to enhance its strategic planning; second, to provide an overview of PT Unilever's approach to designing successful business strategies. The research methodology used in this study involves qualitative research methods, specifically SWOT and PESTEL analyses. The findings of the study reveal that PT Unilever is a highly reputable and diversified company, with a presence in various sectors and markets. This diversification has enabled PT Unilever to maintain its market share and profitability despite intense competition.